Representações identitárias na campanha Keep Walking, Brazil: as relações de cultura e poder na narrativa publicitária - Fraga, Pauline Neutzling (2016)
At the end of 2011, the Scottish whiskey brand Johnnie Walker launched its first one-country only advertising campaign, the Keep Walking, Brazil, signed by the Brazilian advertising agency Neograma/BBH. In addition to the audiovisual Gigante (giant in English), the campaign included 65 other audiovisuals posted at the brand‟s website, which featured interviews with celebrities, considered by the brand as “Brazilian giants”. Keep Walking, Brazil is an example of advertising campaign that used verbal and non-verbal narratives to engage with its public, by highlighting economic and cultural aspects and making references to the national identity. Thus, this research seeks to investigate Brazilian representations in this advertising campaign, as well as to inquire regarding the premises that talking about culture means talking about relationships dominance. Considering historical disputes of interests from different social groups, in order to understand the Brazilian identity and culture, the hypothesis of this research is that, while the representations in the narratives are shown as innovative and positive, they keep the relationships attached to a Brazilian historical determinism of race and socio-cultural environment. Therefore, this study aims to examine the relationships of power that sustain the Brazilian representations in the Keep Walking, Brazil campaign. The specific objectives are: a) To identify the main traces of Brazilian identity based on its recurrent historical representations, especially those present within the media narratives; b)To characterize the narrative of Keep Walking, Brazil, considering the Brazilian cultural context; c) to verify if the Brazilian representations in the narratives reflect the cultural identity; d) To understand how the symbolic forms proposed in the campaign articulate the brand‟s power to control Brazilian cultural aspects within its relationships with Brazilian consumers. This study employed the Thompson‟s method (1995), the depth hermeneutical approach, which helps to interpret the symbolic forms and the originated domination relationships. It was noticed that, at the end of the investigation, Brazilian representations shown in the Keep Walking Brazil campaign did not portray how the country´s cultural identity is actually understood. Therefore, there are still indications of colonialist impressions left in this campaign, even though Brazilian consumers has considered it as a contemporary and innovative representation of national identity.